On becoming creative consumers – user roles in living labs networks. (1st January 2014) - Leminen, Seppo; Westerlund, Mika; Nyström, Anna-Greta
Innovation is no longer solely undertaken by R&D organisations or academic institutions. Users are increasingly participating in all stages of innovation processes. Their role for innovation is especially important in living labs networks, whose idea builds on the co-creation of value with consumers and users. This study explores the conditions under which users co-create innovation in networks characterised by open innovation. In particular, we analyse user roles in 26 living labs in Finland, South Africa, Spain and Sweden. The paper proposes a typology of four user roles in living labs networks: informant, tester, contributor and co-creator. The results suggest that these different user roles form a figurative path towards the creative consumer that proactively co-creates value with companies.